2018
DOI: 10.3171/2018.7.gks181392
|View full text |Cite
|
Sign up to set email alerts
|

Three-stage Gamma Knife treatment for metastatic brain tumors larger than 10 cm3: a 2-institute study including re-analyses of earlier results using competing risk analysis

Abstract: OBJECTIVEThe results of 3-stage Gamma Knife treatment (3-st-GK-Tx) for relatively large brain metastases have previously been reported for a series of patients in Chiba, Japan (referred to in this study as the C-series). In the current study, the authors reappraised, using a competing risk analysis, the efficacy and safety of 3-st-GK-Tx by comparing their experience with that of the C-series.METHODSThis was a retrospective cohort study. Among 1767 patients undergoing GK radiosurgery for brain metastases at Mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 43 publications
(55 reference statements)
0
16
0
Order By: Relevance
“…In this particular case, the positive clinical and radiographic evolution of Met 1 and Met 2 post-RRR were similar to previous reports from other authors and Sinclair et al [24,[26][27][28][29][30] Unfortunately, a deeper analysis of the kinetic effectiveness of RRR compared to single fraction treatments or other oligostaged approaches remains complex and will continue to be a source of bias; indeed, although a few groups have studied the specific effects of stereotactic hypofractionated radiotherapy on tumor kinetics in renal histology, [33,37] to the best of our knowledge, there are no or few studies comparing the ablative dynamics of brain lesions post single fraction versus post hypofractionation. Nonetheless, based on (i) the volumetric data post treatment of this case [Tables 1-3] (ii) our institutional experience, [26][27][28][29][30] and (iii) the available medical literature, [1,24,32,36] we suggest that, in the context of this case, the expeditious and lasting ablative effects triggered by this double prescription technique extended survival. [24,[26][27][28][29][30] Moreover, the fact that our patient developed an ARE at the site of Met 1 and Met 2 despite a hypofractionated approach, suggests that SF-GKRS would have led to greater perilesional edema and possibly substantial radionecrosis resulting in further neurologic damage.…”
Section: Further Aspectsmentioning
confidence: 86%
See 2 more Smart Citations
“…In this particular case, the positive clinical and radiographic evolution of Met 1 and Met 2 post-RRR were similar to previous reports from other authors and Sinclair et al [24,[26][27][28][29][30] Unfortunately, a deeper analysis of the kinetic effectiveness of RRR compared to single fraction treatments or other oligostaged approaches remains complex and will continue to be a source of bias; indeed, although a few groups have studied the specific effects of stereotactic hypofractionated radiotherapy on tumor kinetics in renal histology, [33,37] to the best of our knowledge, there are no or few studies comparing the ablative dynamics of brain lesions post single fraction versus post hypofractionation. Nonetheless, based on (i) the volumetric data post treatment of this case [Tables 1-3] (ii) our institutional experience, [26][27][28][29][30] and (iii) the available medical literature, [1,24,32,36] we suggest that, in the context of this case, the expeditious and lasting ablative effects triggered by this double prescription technique extended survival. [24,[26][27][28][29][30] Moreover, the fact that our patient developed an ARE at the site of Met 1 and Met 2 despite a hypofractionated approach, suggests that SF-GKRS would have led to greater perilesional edema and possibly substantial radionecrosis resulting in further neurologic damage.…”
Section: Further Aspectsmentioning
confidence: 86%
“…Aiming to decrease the risk of SF-GKRS associated ARE, different groups have explored alternative schedules with the aim of reducing toxicity whilst optimising local control; in this framework, volume-staged hypofractionation has become a vivid subject of discussion. [1,[26][27][28][29][30]36] Yamamoto et al conducted a three-stage gamma knife treatment study on 78 patients with e inclusion of underlying radiobiological parameters and inherent physio-mathematical variables are quintessential for triggering key microenvironmental events involving vascular damage and antitumor immunity. e rationale of the procedure can be found elsewhere.…”
Section: Staged Schedulesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in 83 patients, a 3-stage treatment protocol was applied because there was only 1 or a few relatively large tumors or because, even in the event of a tumor being small, it was located at or near very critical anatomic structures (eg, the optic chiasma, hypothalamus, internal auditory canal). 15,16 In these 83 patients, peripheral doses of 9 to 10 Gy were delivered at a 2-week interval. Multiple SRS procedures were required in 664 (31.8%) of our 2089 patients, 2, 3 and 4 or more times in 450, 130 and 84, respectively (IQR, 1-2; maximum, 8).…”
Section: Radiosurgical Techniquesmentioning
confidence: 99%
“…The management of brain metastases is determined by factors such as the number, location and size of tumors, the volume of peritumoral edema, and patient factors such as primary diseases factors and patient age and performance status. A small number of studies have demonstrated single-session and multisessionsession stereotactic radiosurgery (SRS) to be effective and safe in treating large brain metastases (1)(2)(3)(4), however, clinical radiation oncologists are cautious about the use of SRS in their treatment. Although large cerebellum lesions are often amenable to surgical resection, neurological function is difficult to restore.…”
Section: Introductionmentioning
confidence: 99%